Analysis Characteristics Regional Biophysics Air, Water and Condition of North Konawe - Jamal Mukaddas (Postgraduate, University of Mataram, 2025)
Mining activities in North Konawe pose significant environmental challenges due to the exploration and exploitation of natural resources. This study aims to identify and analyze the sustainable efforts undertaken by PT. Sumber Bumiputera in monitoring and managing environmental impacts within its Mining Business License (IUP) area. A qualitative descriptive approach was applied, with data collected through field observations, interviews with stakeholders, and analysis of environmental documents from the company. The findings reveal that PT. Sumber Bumiputera has implemented several environmental management strategies, including land rehabilitation, waste management, and systematic monitoring of water and air quality. These efforts align with existing environmental regulations and aim to mitigate the negative impacts of mining activities. However, there are areas where improvements are necessary, such as enhancing community engagement, strengthening monitoring mechanisms, and increasing compliance with sustainability standards. Strengthening these aspects can contribute to more effective environmental management and long-term ecological balance. This research highlights the importance of continuous environmental monitoring and adaptive management strategies to minimize the adverse effects of mining operations while ensuring sustainable resource utilization.